2020
DOI: 10.3389/fcimb.2020.00371
|View full text |Cite
|
Sign up to set email alerts
|

Perils and Promises of Pathogenic Protozoan Extracellular Vesicles

Abstract: Extracellular vesicles (EVs) are membranous structures formed during biological processes in living organisms. For protozoan parasites, secretion of EVs can occur directly from the parasite organellar compartments and through parasite-infected or antigen-stimulated host cells in response to in vitro and in vivo physiological stressors. These secreted EVs characteristically reflect the biochemical features of their parasitic origin and activating stimuli. Here, we review the species-specific morphology and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 100 publications
(333 reference statements)
0
28
0
Order By: Relevance
“…There has been demonstration of intercommunication between Plasmodium and host cell that was facilitated by ncRNAs (Leitão et al, 2020). It is expected that selected lncRNAs in extracellular vesicles (EV) or secretome (SE) are involved in host-parasite interactions (Olajide and Cai, 2020;Moreno et al, 2021) (Figure 3). However, there is yet to be an explicit definition and identification of parasite lncRNAs in parasite-derived EVs and their possible inter-reactions with those of host origin.…”
Section: Re-definition Of Host-parasite Interactionsmentioning
confidence: 99%
“…There has been demonstration of intercommunication between Plasmodium and host cell that was facilitated by ncRNAs (Leitão et al, 2020). It is expected that selected lncRNAs in extracellular vesicles (EV) or secretome (SE) are involved in host-parasite interactions (Olajide and Cai, 2020;Moreno et al, 2021) (Figure 3). However, there is yet to be an explicit definition and identification of parasite lncRNAs in parasite-derived EVs and their possible inter-reactions with those of host origin.…”
Section: Re-definition Of Host-parasite Interactionsmentioning
confidence: 99%
“…In general, LEVs are exported by either classical or non-classical molecular mechanisms and are involved in the transfer of biologically active molecules, including proteins, lipids, metabolites, miRNAs, and nucleic acids [86,90,91]. Although their role in the infectivity and development of Leishmania is still poorly understood, there is irrefutable evidence that LEVs have important functions, which require further research to clarify aspects such as their molecular pathways and host cells interactions (Figure 5) [8,14,[92][93][94]. The extracellular vesicles effector cargo is known to be delivered into the host target cells, stimulating both pro-and anti-inflammatory immune responses [14,40,[95][96][97].…”
Section: Current and Expected Advances In Leishmania Extracellular Vesicle Researchmentioning
confidence: 99%
“…The immune response is a critical aspect of the infection process and the establishment of the disease through the development of protective immunity associated with the intracellular destruction of the amastigotes by the macrophages, which will depend, in turn, on the induction of an efficient cellular response through the production of cytokines such as IFNγ, interleukins (IL), and TNF-α [20]. In vitro studies have shown that the LEVs of L. (L.) infantum recruited more macrophages and dendritic cells than other extracellular products or the parasite, which reflects the functional response of basal MHC-ll and decreased CD40 and CD 86 [8]. Many recent studies have shown that the presence of LEVs released from L. (L.) donovani modify the IFNγ-induced production of pro-or anti-inflammatory cytokines by cultured human monocytes, favoring the Th1 immune response and the elimination of Leishmania, which leads to the control the infection [1,69,96,118].…”
Section: Leishmania Extracellular Vesicles: What We Know So Farmentioning
confidence: 99%
See 2 more Smart Citations